Organelle reorganization in bovine oocytes during dominant follicle growth and regression. Issue 1 (December 2015) - Dadarwal, D.; Adams, G.; Hyttel, P.; Brogliatti, G.; Caldwell, S.; Singh, Jaswant
Abstract Background We tested the hypothesis that organelles in bovine oocytes undergo changes in number and spatial distribution in a manner specific for phase of follicle development. Methods Cumulus-oocyte-complexes were collected from Hereford heifers by ultrasound-guided follicle aspiration from dominant follicles in the growing phase (n = 5; Day 0 = ovulation), static phase (n = 5), regressing phase (n = 7) of Wave 1 and from preovulatory follicles (n = 5). Oocytes were processed and transmission electron micrographs of ooplasm representing peripheral, perinuclear and central regions were evaluated using standard stereological methods. Results The number of mitochondria and volume occupied by lipid droplets was higher (P < 0.03) in oocytes from regressing follicles (193.0 ± 10.4/1000 μm3 and 3.5 ± 0.7 %) than growing and preovulatory stages (118.7 ± 14.4/1000 μm3 and 1.1 ± 0.3 %; 150.5 ± 28.7/1000 μm3 and 1.6 ± 0.2 %, respectively). Oocytes from growing, static and preovulatory follicles had >70 % mitochondria in the peripheral regions whereas oocytes from regressing follicles had an even distribution. Oocytes from growing follicles had more lipid droplets in peripheral region than in central region (86.9 vs. 13.1 %). Percent surface area of mitochondria in contact with lipid droplets increased from growing (2.3 %) to static, regressing or preovulatory follicle stage (8.9, 6.1 and 6.2 %). The amount, size and distribution of other organelles did not differ among phases (P > 0.11). Conclusions Our hypothesis was supported in that mitochondrial number increased and translocation occurred from a peripheral to an even distribution as follicles entered the regressing phase. In addition, lipid droplets underwent spatial reorganization from a peripheral to an even distribution during the growing phase and mitochondria-lipid contact area increased with follicle maturation.